Konsep Khitbah (Tinjauan Hadis Meminang dalam Kajian Multidisipliner): Penelitian - Antoni Yoseph; Ilyas Husti; Hidayatullah Ismail (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Knowing the authenticity of hadith is indeed different from the Qur'an, because the recording of hadith was only done around the 3rd century Hijri. A span of 200 years, and this is enough to provide the possibility of diversity of hadith texts. Given this historical background, hadith research is still needed to fulfill the intellectual treasure of Muslims in understanding the foundation of a problem through an understanding of the As-Sunnah. One hadith that needs to be reviewed, especially in terms of its evidence is the hadith about the proposal (Khitbah). Proposals in a marriage are highly recommended, but regarding the proposal process itself, it is very diverse, each region has different proposal traditions, so the relevance of this hadith needs to be reviewed again to obtain a more comprehensive meaning of the proposal process. For this research, the author attempted to examine it by asking several problems including what is meant by khitbah, how is the quality of the sanad and matan of the hadith and how the khitbah process is in accordance with the sunnah or rules of the Prophet Muhammad. The author used the Madhu'i method. The object of this research is the method of proposing to a woman and the permissibility of looking at the woman being proposed to. The results of this study explain that the quality of the hadith about proposing to a woman is sahih and can be used as evidence (hujjah) and the quality of the hadith about the permissibility of looking at a woman.